2020
DOI: 10.1002/mde.3212
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cargo and eco‐efficiencies of international container shipping companies: A network‐based ranking approach

Abstract: This study aims to evaluate the cargo and eco-efficiencies of international container shipping companies (CSCs) for the period 2013-2017 for benchmarking purposes. An integration of two-stage network directional distance function and networkbased approach in data envelopment analysis is utilized to distinguish the efficient operators. Results show that most CSCs are highly ranked in the cargo efficiency stage but lowly ranked in the eco-efficiency stage and vice versa. This study emphasizes the strengths and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Regarding a quadratic relationship between CEE and ROA, we find a relationship in the form of a U in Model (10). However, in Models (11), (13), and ( 14), we find an inverted U-shaped relationship between human, relational, innovation capitals, and ROA. From these results, we can conclude that up to a certain level of efficiency, these capitals are the positive factors and that they become restrictive factors of FP beyond that level.…”
Section: Empirical Results Table 4 Presents the Regression Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Regarding a quadratic relationship between CEE and ROA, we find a relationship in the form of a U in Model (10). However, in Models (11), (13), and ( 14), we find an inverted U-shaped relationship between human, relational, innovation capitals, and ROA. From these results, we can conclude that up to a certain level of efficiency, these capitals are the positive factors and that they become restrictive factors of FP beyond that level.…”
Section: Empirical Results Table 4 Presents the Regression Resultsmentioning
confidence: 60%
“…Shipping industry has progressed rapidly because of economic globalization in the past decades [13].…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, these input and output variables remained fundamental for the calculation of CSCs' efficiency. Therefore, in our study, similar inputs and outputs were also chosen based on this foundation of the literature, that is, owned‐in and chartered‐in fleet capacity from Chao (2017), Chao et al (2018), Hsieh et al (2021), Kuo et al (2020), number of employees from Chao et al (2018), Hsieh et al (2021), Kuo et al (2020), Panayides et al (2011), Wang et al (2014), Woo et al (2019), operating costs from Chao (2017), Chao et al (2018), Hsieh et al (2021), Kuo et al (2020), Lun and Marlow (2011), transported volumes from Bang et al (2012), Chao (2017), Chao et al (2018), Hsieh et al (2021), Kuo et al (2020), Lun and Marlow (2011), and revenue from Bang et al (2012), Chao (2017), Chao et al (2018), Hsieh et al (2021), Kuo et al (2020), Lun and Marlow (2011), Panayides et al (2011). Moreover, as COVID‐19 forced companies to undergo a lot of restructuring to meet with new challenges, the factors of cost and efficiency became even more prominent than before.…”
Section: Empirical Studymentioning
confidence: 99%
“…Their bias-corrected results revealed that ten carriers could improve efficiencies on both cargo operations and environment practices. Similar to Kuo et al ( 2020 ), Hsieh et al ( 2021 ) analyzed the efficiency of global container carriers using NSBM and a directional distance function. Findings and implications were similar to those of Kuo et al ( 2020 ).…”
Section: Related Studiesmentioning
confidence: 99%